An Inconsistent Canadian Provincial and Territorial Response During the Early COVID-19 Pandemic - Amelie Cyr; Prosanta Mondal; Gregory Hansen (Frontiers Media S.A., 2021)
Objectives: According to the World Health Organization (WHO), an early and consistent international and national response is needed to control a pandemic's spread. In this analysis, we evaluate the coordination of Canada's early response to the coronavirus (COVID-19) pandemic in terms of public health interventions and policies implemented in each province and territory.Methods: Retrospective data was obtained from publicly accessible websites maintained by federal, provincial and territorial governmental agencies. Consistent with WHO's spreading of the disease pandemic action, individual and community-based public health interventions and policies were the focus. Time of intervention or policy, and COVID-19 cases per million at time of intervention was recorded for each province and territory.Results: Most public health interventions and policies demonstrated wide time ranges of implementation across individual provinces and territories. At time of implementation, there were also wide variations in the number of positive COVID-19 cases in these jurisdictions. Cases per million per implemented day were also not similar across interventions or policy, suggesting that other factors may have been preferentially considered.Conclusions: Whether an earlier and more structured national approach would have lessened the pandemic's burden is uncertain, calls for greater federal coordination and leadership should to examined.